2019
DOI: 10.19184/pk.v7i2.19125
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Suami dengan Kesiapan Persalinan pada Ibu Hamil Usia Remaja di Sukowono, Jember

Abstract: Childbirth readiness is a birth planning process and anticipation of actions to prevent complications. Teenage pregnant women (<20 years) are at risk because at that age the productive and mental functions are immature. This study aimed to analyze the relationship between husband’s support and childbirth readiness of teenage pregnant women in Sukowono Community Health Center, Jember. The study used correlational approach with cross-sectional study design. Sample size was 34 teenage pregnant women, collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 3 publications
3
12
0
1
Order By: Relevance
“…The results of this study are aligned with a study conducted at Puskesmas Nanggalo, Padang, in which there was a relationship between husband support and adherence to consumption of Fe tablets [30]. Hence, there was a relationship between husband support and anxiety of pregnant women overcoming the birth delivery of their first child during the third trimester in some birth delivery clinics in Purwokerto [17]. If the husband provided instrumental support in preparing the budget for the cost of birth delivery, the wife prepares for the baby's needs [11].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The results of this study are aligned with a study conducted at Puskesmas Nanggalo, Padang, in which there was a relationship between husband support and adherence to consumption of Fe tablets [30]. Hence, there was a relationship between husband support and anxiety of pregnant women overcoming the birth delivery of their first child during the third trimester in some birth delivery clinics in Purwokerto [17]. If the husband provided instrumental support in preparing the budget for the cost of birth delivery, the wife prepares for the baby's needs [11].…”
Section: Discussionsupporting
confidence: 84%
“…In this case, the husband is the wife's life partner (the father of the children) in which they have full responsibility in the family. They are highly demanded both as a breadwinner and supporters in various policies [17]. Research on husbands' support of young mothers' motivation in exclusive breastfeeding showed that most husbands (92.3%) provided good support [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations